Hidden nature. - Ong, Chao Yan. (2013)
My project is about hidden nature, the result of an urbanized environment, and the exploration of formal elements in landscape. Since the modern re-development of Singapore, economic demands have caused rural areas to be torn up and are used for other purposes such as public housing for increasing population, shopping malls and high rise buildings. Urbanization in Singapore has eliminated most primary rainforest on the main island, resulting in the island being systematically transformed. My project focus on this human-altered landscape and the irreversible transformation of the environment.